THE CODE-SWITCHING ANALYSIS ON INDONESIAN BOY BAND AND GIRL BAND SONGS - Bhasmanara, Whikanta; Ratminingsih, Ni Made; Sari, Rima Andriani (Lingua Scientia, 2025)
This research was conducted to analyze the code-switching phenomenon on Indonesian boy band and girl band songs especially the type of code-switching by using Poplack’s (1980) theory and the function of code-switching by using the theory from Apple and Musyken (2005). This research used a descriptive qualitative method. The data source were songs from 2 Indonesian boy bands and 2 Indonesian girl bands as these bands often use two languages in most of their songs. The object of this research was 9 songs from 4 Indonesian boy bands and girl bands. This research also used the observation technique to collect the data that was gathered from the YouTube platform. Content analysis was used to analyze the data. The results showed that the most common type of code-switching found in Indonesian boy band and girl band songs was intra-sentential switching followed by the second most common type of code-switching inter-sentential switching. Only 1 data was found as tag-switching. This research provides insight of the use of code-switching in Indonesian songs, particularly on the types and the functions.